Guillain-Barré syndrome associated with monosialotetrahexosylganglioside: three cases study and literature review - Ke JIANG; Xue-feng WANG; Ke-bin ZENG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2013)
Background Monosialotetrahexosylganglioside (GM1) is a kind of ganglioside extracted from the neural cells of pig brain, which involves in the pathophysiological processes of neurogenesis, and plays an important role in neural formation, growth and differentiation. GM1 is widely used in the treatment for vascular brain injury and traumatic brain and spinal cord injury, promoting and protecting the recovery of nerve cells. Besides, it can improve the behavior disorders of patients with Parkinson's disease. However, as it is widely used in clinical practice, its adverse reaction has been gradually discovered. There is some evidence to suggest Guillain-Barré syndrome (GBS) may occur after GM1 injection intravenously. Both clinical manifestations and possible mechanism of GBS associated with GM1 are unclear, and need further study. Methods Three cases of GBS associated with GM1 were clinically observed including cerebrospinal fluid (CSF) testing and nerve conduction studies. These cases were analyzed and subjected to assessment with literature review. Results Three male patients (with the age 39-65) of GBS were observed after injection of GM1 intravenously. At 9-14 days, they developed weakness of all limbs and were unable to stand upright with decreased muscle tone in limbs and absent deep tendon reflexes, accompanied by dyspnea (1 case), albuminocytological dissociation (1 case) and axonal degeneration of peripheral nerve (1 case). Conclusion GBS may occur occasionally in patients treated with GM1 injection intravenously for 9-14 days, and the prognosis is not favorable. The possible mechanism is that exogenous gangliosides could be immunogenic and may occasionally result in neural axonal degeneration.